Clinical and economic analysis of using the thrombodynamics test in patients undergoing treatment with assisted reproductive technologies in the Russian Federation - D. G. Shchurov; V. S. Dombrovskiy (Фармакоэкономика)
Objective: early assessming the clinical and economic efficacy of the thrombodynamics test in infertile patients undergoing treatment with assisted reproductive technologies (ART), as well as the impact of this test on the health care budget of the Russian Federation.Material and methods. The study was carried out on the basis of statistical data on the number of ART cycles, the proportion of patients with hypercoagulation and normocoagulation of blood, data on the clinical effectiveness of ART programs in Russia, including the dependency on the status of blood coagulation, as well as cost data. The analysis was carried out according to three scenarios: 1) thrombodynamics test with subsequent correction of the revealed hypercoagulability status before in vitro fertilization (IVF); 2) thrombodynamics test with the subsequent refusal to perform IVF in patients with hypercoagulability; 3) thrombodynamics test with subsequent correction of the revealed hypercoagulability status before the start of the frozen-thawed embryo transfer. The criteria for clinical effectiveness were the following indicators: the number of children born and the number of potentially saved life years. Clinical and economic efficacy criteria included: total direct medical costs; incremental cost-effectiveness ratio (ICER); changes in the amount of total direct medical costs; resizing effectively and ineffectively spent funds.Results. The use of the thrombodynamics test will potentially increase the number of children born by 21–33 children and the number of years of life saved, with discounting considered, within the range of 923–1448 years per 1000 ART cycles, depending on the study scenario. The smallest ICER values were observed in Scenario 2, and amounted to 112,120 rubles for 1 child born and 2519 rubles for 1 saved year of life. The highest ICER values were obtained in Scenario 1: 275,576 rubles for 1 child born and 6191 rubles for 1 saved year of life. The use of the thrombodynamics test in women with infertility before ART in Russia will require an increase in direct medical costs from 174 to 425 million rubles (by 1–5% of the initial level of costs) in absolute terms, depending on the chosen scenario with a time horizon of 1 year.Conclusion. Due to the expected significant improvement in treatment outcomes and the small amount of additional costs, the introduction of the thrombodynamics test into the routine practice of assessing blood clotting in infertile patients before the start of the ART cycle is potentially cost-effective, but further clinical studies are required for a more accurate economic assessment.